Fading Solidarity Among Women on Tiktok: A Phenomenological Analysis of the "Girls Support Girls" Movement Among Adolescents - Ranniko Dinda Artanti; Muh. Najih Farihanto (Journal of Social Research, 2026)
The Girls Support Girls movement on TikTok initially emerged as a form of inclusive solidarity among women but has shifted toward selective and conditional support. This study aims to understand the forms of female support, the meaning of conditional support, and the factors causing the decline of female solidarity in the Girls Support Girls movement on TikTok from the perspective of young women. This research employs a qualitative approach using a descriptive phenomenological method. Data were collected through semi-structured in-depth interviews with four female participants aged 19–25 years who actively use TikTok and have experience interacting with content related to the Girls Support Girls movement. The findings reveal three main results: (1) support among women on TikTok most often appears in the form of positive validation, encouragement, and defense; (2) such support is perceived as selective and conditional, depending on appearance, social norms, and specific situations; and (3) female solidarity easily fades due to insecurity, competition, and pressure from beauty standards that transform relationships among women into social comparisons. This study confirms that although Girls Support Girls is understood as emotional support among women, its practice is heavily influenced by the social context on TikTok, where validation, social judgment, and aesthetic pressure become the main factors shaping support dynamics.